Insights into innate immune cell evasion by Chlamydia trachomatis - Wang, Xinglv; Wu, Hongrong; Fang, Chunxia; Li, Zhongyu (Frontiers in Immunology, 2024)
Chlamydia trachomatis, is a kind of obligate intracellular pathogen. The removal of C. trachomatis relies primarily on specific cellular immunity. It is currently considered that CD4 + Th1 cytokine responses are the major protective immunity against C. trachomatis infection and reinfection rather than CD8 + T cells. The non-specific immunity (innate immunity) also plays an important role in the infection process. To survive inside the cells, the first process that C. trachomatis faces is the innate immune response. As the "sentry" of the body, mast cells attempt to engulf and remove C. trachomatis. Dendritic cells present antigen of C. trachomatis to the "commanders" (T cells) through MHC-I and MHC-II. IFN-γ produced by activated T cells and natural killer cells (NK) further activates macrophages. They form the body's "combat troops" and produce immunity against C. trachomatis in the tissues and blood. In addition, the role of eosinophils, basophils, innate lymphoid cells (ILCs), natural killer T (NKT) cells, γδT cells and B-1 cells should not be underestimated in the infection of C. trachomatis. The protective role of innate immunity is insufficient, and sexually transmitted diseases (STDs) caused by C. trachomatis infections tend to be insidious and recalcitrant. As a consequence, C. trachomatis has developed a unique evasion mechanism that triggers inflammatory immunopathology and acts as a bridge to protective to pathological adaptive immunity. This review focuses on the recent advances in how C. trachomatis evades various innate immune cells, which contributes to vaccine development and our understanding of the pathophysiologic consequences of C. trachomatis infection.